2010
DOI: 10.1039/c001350a
|View full text |Cite
|
Sign up to set email alerts
|

Silver catalyzed cascade synthesis of alkaloid ring systems: concise total synthesis of fascaplysin, homofascaplysin C and analogues

Abstract: A silver catalyzed and microwave assisted one-pot cascade synthesis provides efficient access to diverse alkaloid-inspired scaffold classes, and a concise and efficient total synthesis of homofascaplysin C and fascaplysin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…Similarly, a cascade reaction sequence involving silvercatalyzed cycloisomerization of acetylenic aldehydes as the key transformation was recently explored in the synthesis of diverse alkaloid ring systems. [55] Indoloisoquinolines, a medicinally significant class of molecules known for their anticancer properties, were readily and efficiently generated by using this cascade approach. Thus, the imine generated from an acetylenic benzaldehyde 55 and an aniline with a pendant nucleophile 56 underwent the key silvercatalyzed cycloisomerization reaction under microwave conditions to yield the isoquinolinium cations 58.…”
Section: Bios In the Development Of Compound Collectionsmentioning
confidence: 99%
“…Similarly, a cascade reaction sequence involving silvercatalyzed cycloisomerization of acetylenic aldehydes as the key transformation was recently explored in the synthesis of diverse alkaloid ring systems. [55] Indoloisoquinolines, a medicinally significant class of molecules known for their anticancer properties, were readily and efficiently generated by using this cascade approach. Thus, the imine generated from an acetylenic benzaldehyde 55 and an aniline with a pendant nucleophile 56 underwent the key silvercatalyzed cycloisomerization reaction under microwave conditions to yield the isoquinolinium cations 58.…”
Section: Bios In the Development Of Compound Collectionsmentioning
confidence: 99%
“…Recently some reports have shown that silver salt catalysts or co-catalysts efficiently promoted organic reactions [13,14]. Significant development of palladium(0)/silver salt catalyzed cross-coupling reactions has occurred only in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…The intermediates also lead to interesting carbazoles,14 dihydroisoquinolines15 and isoquinolines 16. Furthermore, they have been applied in the total synthesis of azaphilones,4c,17 fascaplysin,18 heliophenanthrone,5a and (+)‐ochromycinone 19…”
Section: Introductionmentioning
confidence: 99%